2022
DOI: 10.18632/aging.204269
|View full text |Cite
|
Sign up to set email alerts
|

Fetal programming: in utero exposure to acrylamide leads to intergenerational disrupted ovarian function and accelerated ovarian aging

Abstract: In this study we investigated the effects of multigenerational exposures to acrylamide (ACR) on ovarian function. Fifty-day-old Wistar albino female rats were divided into the control and ACR-treated groups (2.5, 10, and 20 mg/kg/day) from day 6 of pregnancy until delivery. The obtained females of the first (AF1) and second generation (AF2) were euthanized at 4 weeks of age, and plasma and ovary samples were collected. We found that in utero multigenerational exposure to ACR reduced fertility and ovarian funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…In fact, there was a significant increase in ovary weight at the higher doses for both the first and second generations compared to the control group. This finding is in agreement with previous reports showing that treatment with some substances, such as acrylamide, sodium fluoride, BPA, and nonylphenol, led to an increase in ovary weight [ 39 , 40 , 41 , 42 ]. Although cyclic fluctuations are connected to ovarian function during the estrous cycle, it is known that ovarian weight does not significantly change in normal rats.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, there was a significant increase in ovary weight at the higher doses for both the first and second generations compared to the control group. This finding is in agreement with previous reports showing that treatment with some substances, such as acrylamide, sodium fluoride, BPA, and nonylphenol, led to an increase in ovary weight [ 39 , 40 , 41 , 42 ]. Although cyclic fluctuations are connected to ovarian function during the estrous cycle, it is known that ovarian weight does not significantly change in normal rats.…”
Section: Discussionsupporting
confidence: 93%
“…In line with our study, in a study, female rats were exposed to different doses of ACR, found that ACR causes a significant decrease in ovarian weight. This study also stated the possible reproductive toxic effects of ACR in female mice[19]. Petersson and colleagues stated the following effects of a diet containing ACR.…”
mentioning
confidence: 67%
“…V refers to the volume component, t is the section thickness, a (p) is the area of one point (1000 μ), ΣP is the total number of points counted in the component, and M is the linear magnification [19]. The total number of primordial, primary, secondary Graafian, and atresian follicles was estimated using the physical dissector counting method.…”
Section: H and E Stainingmentioning
confidence: 99%
“…Acrylamide and its metabolites are also known to form adducts with proteins and DNA, raising concerns for genotoxicity [14]. Moreover, evidence of the adverse developmental effects of acrylamides on ovarian function and fertility spanning at least two consecutive generations underlines the necessity for more targeted strategies during pregnancy, including following a healthy diet and eliminating consumption of acrylamide-rich products [15].…”
Section: Introductionmentioning
confidence: 99%